Study on Patient’s Perception on Medication Counseling at Community Pharmacy in Sub-urban Area of Nepal - Shrestha, U.; Koju Shrestha, R.; Biswokarma, A. K.; Koju, P.; Shrestha, S.; Shakya Shrestha, S. (Kathmandu University Medical Journal, 2022)
Background Community pharmacists are the primary contact point in a healthcare system who provide medication information to the patients and enable them to make appropriate decision regarding their therapy. Hence, this study explored patients’ perception of community pharmacist based on medication counseling. Objective To study patient’s perception on medication counseling by community pharmacist at Manohara Municipality, Kathmandu, Nepal Method A cross sectional study was conducted from November 2020 to April 2021 in population visiting pharmacies of Kageshwori Manohara Municipality of Kathmandu valley. A total of 384 participants included in the study were surveyed using a structured questionnaire exploring the content of medication counseling, level of satisfaction on counseling and use of various means of counseling. Descriptive data were presented in frequencies and percentages using EXCEL 2016. Result This study enrolled 384 participants out of which 354, 92.19% received medication counseling. The main reason of pharmacy visit was to obtain over the counter medicines, 262, 68.23%. Majority of the participants rated satisfied with informations provided on use of medication 218, 56.77%, duration of therapy 261, 67.97%, about side effects 211, 54.95% and on action to be taken following side effects 246, 64.06%. Most of the participants rated satisfied with counseling on storage 189, 49.22% and for referral 250, 65.10% while 201, 52.34% participants rated highly satisfied with advice on lifestyle and dietary changes required. Conclusion This study concludes that the patients’ perception regarding the medication counseling by community pharmacist was acceptable. Thus pharmacists should be encouraged to support patients with their medication to promote patient care.